Pendidikan Islam Multikultural sebagai Upaya Meneguhkan Moderasi Islam di Pesantren - Ratnawati, Siti Rohmaturrosyidah; Wathoni, Kharisul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
Violence, conflict, and terrorism in the name of religion often occur in Indonesia. These led to the emergence of prejudice and public perception that pesantren as educational institution which contributed to growing the seeds of fanaticism and radicalism. However, not all pesantrens act as they think and accuse. There are still a lot of pesantrens that remain consistent in instilling the values of Islam’s moderation in their students to this day, including Pondok Modern Arrisalah, one of pesantrens in Ponorogo that has implemented multicultural Islamic education because it has many students with different backgrounds in terms of region, ethnicity, language, culture, and class. This study aims to describe and analyze the implementation of multicultural Islamic education at Pondok Modern Arrisalah Slahung Ponorogo as an effort to strengthen the moderation vision of Islam to its students. The researcher in this case used the type of field research and a qualitative descriptive approach. The research data were collected through interview, observation, and documentation techniques. The results show that Pondok Modern Arrisalah has implemented multicultural Islamic education which can be seen from various aspects, namely the curriculum, supporting programs and activities, the creation of a religious-multicultural culture and gender relation in it.